PENINGKATAN DISPOSISI MATEMATIS DENGAN PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL THINKING ALOUD PAIRS PROBLEM SOLVING (TAPPS) BERBASIS MULTIMEDIA - Wanabuliandari, Savitri (Universitas Muria Kudus, 2016)
This research is aimed to develop the mathematics learning materials quadrilateral with amodel-based Multimedia TAPPS, so that it becomes a valid, practical and effective learningdevice. The study is also aimed to determine the increase of mathematical disposition. Thedevelopment of learning device is done by using 4-D Thiagarajan model, which has been modifiedwhich include Define, Design, and Develop. The types of learning devices which developed aresyllabus, lesson plans, worksheets, and Multimedia. The validity of the learning device isdetermined based on the expert validation. The Practicality of learning device can be seen fromthe response of the students, teachers' responses and management teacher learning in theclassroom. The effectiveness of learning can be obtained by doing a test device.